The International protection for victims of human trafficking (Journal of Human Sciences, 2025)
This study aims to clarify the mechanisms contained in international agreements to protect and care for victims of the crime of human trafficking, by presenting the rules and procedures included in these agreements that enshrine this protection, as this protection is represented in direct protection, and indirect protection through which the international community has paid attention to the situation of victims of human trafficking and the circumstances surrounding them We also addressed the nature of the crime of human trafficking and all its related characteristics and forms, relying on the descriptive approach. At the conclusion of this research, we concluded that the role of international agreements in protecting victims of human trafficking cannot be denied. However, with the steady increase and continuity of this phenomenon, the international community must be more willing to establish comprehensive and effective protection for victims of human trafficking.